Pendidikan dan Pengembangan Anak melalui Pondok Belajar dan Alat Peraga Edukatif di Desa Lunto Barat - Wiwin Ratna Sari; Muthia Fernanda Putri; Rahma Dahtul Asih (CV. ITTC INDONESIA, 2026)
This study aims to describe the implementation of a children’s learning center and the use of educational teaching aids (APE) in improving children's learning interest and understanding in Lunto Barat Village, Lembah Segar District, Sawahlunto City. The background of this study is based on the limited variety of learning methods and lack of educational media for children in rural areas. This study employed a descriptive qualitative approach conducted during the January 2026 community service program (KKN). Data were collected through direct observation and documentation during the learning activities. The findings show that children demonstrated high enthusiasm and active participation in learning activities, including basic literacy and introductory Japanese language lessons. The use of APE on the topic of the pillars of faith helped children understand abstract concepts more concretely and effectively. The program also improved social interaction among children and created a more engaging learning environment. This study implies that simple, interactive, and community-based educational programs can effectively support children's learning development in rural areas and can be adapted for similar contexts.